A thick gauge l555m pipeline steel hot-rolled coil with low yield ratio and excellent ctod performance and a manufacturing method thereof

CN122898801APending Publication Date: 2026-10-13ANGANG STEEL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202611192950.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0011]综上所述,目前已公开的关于555MPa级管线钢的资料虽然较多,但在成分上多数依赖于合金元素Mo和Cr的添加;在韧性指标上多数仅进行冲击和落锤试验,对CTOD性能指标研究较少

Benefits of technology

1)采用Mg-Ca-Ce-Ti复合处理方法在钢中引入大量的纳米级氧化物粒子,阻碍铸坯加热和保温过程中奥氏体晶粒的长大,因而即使在较高的加热温度下也能获得细小的奥氏体晶粒,减轻了轧机的负荷,有利于有粗轧大压缩比工艺的实施。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898801A_ABST
    Figure CN122898801A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of pipeline steel production, and particularly relates to a thick-specification L555M pipeline steel hot-rolled coiled sheet with low yield ratio and excellent CTOD performance and a manufacturing method thereof.The chemical components in the steel are as follows in percentage by weight: C: 0.040%-0.060%, Si: 0.08%-0.25%, Mn: 1.65%-1.85%, P: ≤0.019%, S: ≤0.005%, Nb: 0.065%-0.080%, V: 0.015%-0.035%, Ti: 0.012%-0.022%, Ni: 0.10%-0.20%, Als: 0.010%-0.020%, Ca: 0.002%-0.003%, Mg: 0.001%-0.002%, Ce: 0.002%-0.003%, N: ≤0.007%, and the balance being Fe and inevitable impurities.The yield strength is 560-600 MPa, the tensile strength is 700-750 MPa, the yield ratio is ≤0.80, the elongation is ≥30%, the average impact energy at-60 DEG C is ≥300 J, the average falling weight shear area at-25 DEG C is ≥85%, and the CTOD value at-25 DEG C is ≥1.40 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pipeline steel production technology, and in particular to a thick-gauge L555M pipeline steel hot-rolled coil with a low yield strength ratio and excellent CTOD performance, and its manufacturing method. Background Technology

[0002] L555M (X80M) grade pipeline steel, due to its high strength and good toughness, has become the preferred material for high-pressure, high-flow-rate oil and gas pipelines. With the continuous increase in pipeline transport pressure and the development of harsh service environments such as oceans and polar regions, engineering projects are placing more stringent requirements on the performance of pipeline steel. Among these requirements, in addition to traditional strength and low-temperature toughness indicators, a low yield strength ratio and excellent crack tip opening displacement (CTOD) characteristics have become key indicators for evaluating the fracture resistance and crack arrest capabilities of pipeline steel.

[0003] The yield strength ratio reflects a material's strain hardening capacity and plastic reserve. A low yield strength ratio means the material has a larger plastic deformation space from yield to fracture, which is important for preventing pipeline overload failure and resisting plastic deformation caused by geological disasters. However, in existing technologies, to meet the high strength requirements of L555M grade, multi-element microalloying and complex thermomechanical control (TMCP) processes are usually adopted. Although high strength can be obtained, this often leads to a high yield strength ratio, which is usually difficult to stably control below 0.90, thus limiting the material's strain capacity. On the other hand, the CTOD value, as a key evaluation parameter of elastoplastic fracture toughness, is directly related to the safe service life of pipelines under defective conditions, especially in scenarios requiring high service reliability, such as cold regions or the seabed. In particular, for thick-gauge hot-rolled coils, due to the limited rolling compression ratio and thickness-direction microstructure differences, segregation or coarse microstructure is easily generated in the center of the thickness, resulting in CTOD toughness, especially thickness-direction toughness, being much lower than the base material level.

[0004] For thick-gauge L555M pipeline steel, achieving a low yield strength ratio and high CTOD toughness simultaneously while maintaining high strength has long been a technical challenge in this field. Some existing technologies improve toughness by adding a large amount of the expensive alloying element Mo, but this significantly increases manufacturing costs. Therefore, developing a technical solution that does not rely excessively on expensive alloys and has strong process adaptability to manufacture thick-gauge L555M pipeline steel hot-rolled coils with both low yield strength ratio and excellent CTOD performance has significant industrial application value.

[0005] The following is a brief introduction to the patents and literature related to 555MPa grade pipeline steel that have been published domestically and internationally, but they are all significantly different from this invention, as detailed below: 1) Chinese Patent Document CN120443068A, a low yield strength ratio, low temperature, high toughness X80MO pipeline steel plate and its manufacturing method. The composition contains: C: 0.020%~0.039%, Mn: 1.50%~1.60%, Si: 0.31%~0.40%, S≤0.001%, P≤0.010%, Nb: 0.041%~0.080%, Ti: 0.008%~0.030%, V: ≤0.030%, Alt: ≤0.06%, N: ≤0.010%, O: ≤0.006%, Mo: 0.10%~0.30%, Cu≤0.30%, Ni: 0.15%~1.50%, Cr: 0.15%~0.45%, Ca: ≤0.01%. This invention pertains to the field of medium and heavy plates. It incorporates higher levels of Mo, Cr, and Cu in its alloy composition design, while maintaining extremely low levels of P and S, resulting in higher alloy costs and a compositional difference from this invention. Furthermore, this invention has more lenient requirements for yield ratio and CTOD, with a yield ratio not exceeding 0.83 and a CTOD value of only ≥0.3mm at -25℃, which differs significantly from this invention.

[0006] 2) Chinese patent document CN117230287A, process method for producing X80 pipeline steel of extreme specifications during high water temperature season. The composition contains C: 0.03%~0.04%, Si: 0.10%~0.20%, Mn: 1.60%~1.70%, P≤0.010%, S≤0.001%, Alt: 0.025%~0.035%, N: ≤0.0030%, O: ≤0.0010%, Cr: 1.0%~1.2%, Ti: 0.10%~0.15%, V: 0.035%~0.055%. This invention adds a higher content of Cr and V to the alloy composition design, which is different from the composition of this invention; at the same time, the heating temperature designed by this invention is lower, the rolling mill load is high, which is not conducive to mass production; in addition, the yield ratio index required by this invention is more lenient, with a yield strength ratio not higher than 0.85, which is significantly different from that of this invention; in terms of toughness, only impact and drop hammer tests were conducted, without paying attention to CTOD performance.

[0007] 3) Chinese patent document CN104073744A, High-toughness X80 pipeline steel coil with thickness ≥18.5mm and its production method. The composition includes C: 0.025%~0.055%, Si: 0.10%~0.35%, Mn: 1.85%~2.00%, P≤0.012%, S≤0.0015%, Cu: 0.15%~0.30%, Cr: 0.20%~0.40%, Ni: 0.15%~0.40%, Mo: 0.20%~0.40%, Nb: 0.070%~0.095%, V: 0.015%~0.040%, Ti: 0.005%~0.025%, Al: 0.015%~0.045%, N: ≤0.008%, Ca: 0.0010%~0.0040%. This invention adds a higher content of Mo, Cr, and Cu to the alloy composition design, resulting in a higher alloy cost and a different composition from this invention. At the same time, the impact test temperature of this invention is only -20℃, and the drop hammer test temperature is only -15℃, with a more lenient low-temperature toughness index.

[0008] 4) Chinese Patent Document CN103276314A, a low yield strength ratio and high toughness X80 pipeline steel plate and its manufacturing method. The composition includes C: 0.036%~0.060%, Si: 0.15%~0.40%, Mn: 1.65%~1.90%, P≤0.012%, S≤0.0015%, Ni: 0.15%~0.40%, Mo: 0.10%~0.30%, Cr: 0.30%~0.50%, Cu: 0%~0.30%, Nb: 0.035%~0.055%, Ti: 0.005%~0.030%, Al: 0.020%~0.050%, N: ≤0.008%. This invention adds a relatively large amount of Mo, Ni, Cr, and Cu, resulting in a high alloy cost; furthermore, this invention requires quenching and tempering after rolling, making the production process complex and energy-intensive. Furthermore, the yield ratio required by the invention is only no higher than 0.82, which is significantly different from that of the present invention.

[0009] 5) Chinese patent document CN102851614A discloses a hot-rolled coil of X80 pipeline steel with low yield strength ratio and its manufacturing method. The composition includes C: 0.030%~0.055%, Si: 0.15%~0.30%, Mn: 1.60%~1.85%, Nb: 0.080%~0.120%, Cr: 0.20%~0.35%, Ni: 0.15%~0.25%, Cu: 0.18%~0.28%, Ti: 0.015%~0.030%, Als: 0.015%~0.050%, P≤0.018%, S≤0.0030%, and N≤0.005%. This invention adds Cr and Cu to the composition, which differs from the design of this invention. Furthermore, the high-temperature heating process used in this invention's casting is detrimental to grain refinement and results in high energy consumption during production.

[0010] 6) Chinese patent document CN108546885A discloses an L555M pipeline steel with excellent low-temperature toughness and its manufacturing method. The composition includes C: 0.045%~0.065%, Si: 0.10%~0.25%, Mn: 1.66%~1.76%, Nb: 0.055%~0.075%, Ti: 0.010%~0.025%, Mo: 0.21%~0.29%, Cr: 0.11%~0.19%, Ni: 0.05%~0.15%, Als: 0.015%~0.045%, P≤0.018%, S≤0.0030%, and N≤0.005%. This invention adds a large amount of Mo to the composition, resulting in higher alloy costs. Furthermore, the yield ratio requirement of this invention is relatively lenient, with a yield strength ratio not exceeding 0.90, which differs significantly from the present invention.

[0011] In summary, although there is a considerable amount of publicly available information on 555MPa grade pipeline steel, most of it relies on the addition of alloying elements Mo and Cr in terms of composition; and in terms of toughness indicators, most of it only involves impact and drop hammer tests, with relatively little research on CTOD performance indicators.

[0012] This invention breaks with traditional pipeline steel alloy composition design. By introducing nanoscale oxide particles through Mg-Ca-Ce-Ti composite treatment, it inhibits austenite grain growth during billet heating and holding. In the rolling process, it increases the single-pass compression ratio of rough rolling and reduces the rolling speed, allowing sufficient dynamic recrystallization of austenite from the surface to the core. After rolling, a short relaxation time promotes the formation of a small amount of soft phase to reduce the yield strength ratio. At the same time, it introduces a large number of subgrain boundaries into the grains, which, together with the oxide particles, serve as nucleation sites to promote the formation of ultrafine needle-like ferrite. Finally, it obtains thick-gauge L555M pipeline steel hot-rolled coil products with low yield strength ratio and high CTOD performance. Summary of the Invention

[0013] The purpose of this invention is to overcome the above-mentioned problems and provide a thick-gauge L555M pipeline steel coil with excellent CTOD performance and a low yield strength ratio, as well as its production method. Its yield strength is 560~600MPa, tensile strength is 700~750MPa, yield strength ratio is ≤0.80, elongation is ≥30%, average impact energy at -60℃ is ≥300J, average drop shear area at -25℃ is ≥85%, and CTOD value at -25℃ is ≥1.40mm.

[0014] To achieve the above objectives, the present invention employs the following technical solution: A thick-gauge L555M pipeline steel hot-rolled coil with low yield strength ratio and excellent CTOD performance. The chemical composition of the steel, by weight percentage, is as follows: C: 0.040%~0.060%, Si: 0.08%~0.25%, Mn: 1.65%~1.85%, P≤0.019%, S≤0.005%, Nb: 0.065%~0.080%, V: 0.015%~0.035%, Ti: 0.012%~0.022%, Ni: 0.10%~0.20%, Als: 0.010%~0.020%, Ca: 0.002%~0.003%, Mg: 0.001%~0.002%, Ce: 0.002%~0.003%, N≤0.007%, with the balance being Fe and unavoidable impurities.

[0015] The hot-rolled coil has a yield strength of 560~600MPa, a tensile strength of 700~750MPa, a yield strength ratio of ≤0.80, an elongation of ≥30%, an average impact energy of ≥300J at -60℃, an average drop shear area of ​​≥85% at -25℃, and a CTOD value of ≥1.40mm at -25℃.

[0016] The thickness of the hot-rolled coil is 21.4~22mm, and the microstructure consists of polygonal ferrite + acicular ferrite + Mao islands.

[0017] This invention, without adding Mo and Cr, utilizes the concept of second-phase particle pinning and increased acicular ferrite nucleation sites. Through Mg-Ca-Ce-Ti microalloying, a large number of dispersed nanoscale composite oxide second-phase particles are introduced into the steel, suppressing austenite grain growth during billet heating and holding. A single-pass, low-speed, high-compression-ratio process is employed in the rough rolling stage to fully refine the austenite grains throughout the thickness direction. After rolling, a 15-25s relaxation followed by accelerated cooling allows the formation of dislocation substructures within the grains and the second-phase particles to provide numerous nucleation sites for ferrite, ultimately resulting in a fine polygonal ferrite + acicular ferrite microstructure. This achieves a good balance between hardness and softness, significantly reducing the yield strength ratio of the plate and greatly improving its low-temperature toughness, giving the plate and coil excellent CTOD performance.

[0018] The reasons for using chemical elements in this invention are as follows: Carbon (C) is the most fundamental and economical contributor to strength in steel, significantly enhancing yield strength and tensile strength primarily through interstitial solid solution mechanisms. However, its application in pipeline steel is strictly limited because increased carbon content drastically worsens weldability and low-temperature toughness. Higher carbon content leads to hardening of the weld heat-affected zone, increasing susceptibility to cold cracking. Simultaneously, carbon promotes the formation of harmful brittle phases such as pearlite, impairing the steel's crack-arresting toughness. Therefore, high-performance pipeline steels generally employ "ultra-low carbon" or "low carbon" designs. This invention controls the C content to 0.040%~0.060%.

[0019] Silicon (Si): During the smelting stage, silicon is a highly efficient deoxidizer, preferentially combining with oxygen in molten steel to form SiO2, thereby purifying the steel and reducing bubbles, which is crucial for ensuring the purity of the steel. In steel, silicon exists in the matrix in the form of substitutional solid solution, providing a significant solid solution strengthening effect and effectively improving strength. However, a high silicon content can significantly impair the weldability of steel, increasing the hardening tendency and cold cracking sensitivity of the weld heat-affected zone, and reducing the toughness of this area. Therefore, this invention controls the Si content to 0.08%~0.25%.

[0020] Mn: Manganese is a highly efficient solid solution strengthening element that can stably improve strength. Secondly, manganese can significantly lower the austenite-ferrite phase transformation temperature. This effect promotes the formation of fine acicular ferrite, bainite, and other low-temperature transformation structures during cooling. These structures have extremely high dislocation density and fine substructure, forming the microstructure basis for achieving high strength and high toughness in pipeline steel. Excessive manganese content will exacerbate center segregation in continuously cast billets, forming manganese-rich banded structures, severely deteriorating the transverse toughness of the steel. Therefore, this invention controls the Mn content to 1.65%~1.85%.

[0021] P, S, and N are impurity elements in steel. Ideally, their content should be as low as possible, but excessively low content will increase production costs. In this invention, P is ≤0.019%, S is ≤0.005%, and N is ≤0.007%.

[0022] Nb: During the high-temperature rolling stage, niobium, in the form of solid-solution atoms or fine Nb(C,N) precipitates, strongly inhibits the recrystallization of austenite grain boundaries and grain growth, allowing rolling to take place in the non-recrystallized austenite region, thus obtaining fine grains after phase transformation. During the subsequent cooling process, niobium precipitates in the matrix as extremely fine NbC nanoparticles, producing a significant precipitation strengthening effect. By precisely controlling the amount of niobium added and the process, an optimal combination of fine-grain strengthening and precipitation strengthening can be achieved, resulting in a significant increase in strength while simultaneously improving toughness. Therefore, this invention controls the Nb content to 0.065~0.080%.

[0023] Vanadium (V) reacts with carbon and nitrogen in steel to form nanoscale vanadium precipitates. These precipitates not only pin austenite grain boundaries, hindering austenite grain growth during reheating and refining the room-temperature microstructure, but also enhance strength through a strong precipitation strengthening effect. In this invention, the V content is controlled at 0.015%~0.035%.

[0024] Ti: Under low-alumina conditions, titanium can combine with oxygen in steel to form TiO, TiO2, and Ti2O3 particles, which have better high-temperature thermal stability than TiN. During continuous casting and heating, they effectively pin austenite grain boundaries, preventing excessive growth and providing a fine and uniform starting point for subsequent controlled rolling. Furthermore, the oxides can absorb Mn from the surrounding matrix, leading to the formation of a certain range of Mn-depleted regions around the particles, thereby promoting the nucleation of acicular ferrite. Therefore, this invention controls the Ti content to 0.012%~0.022%.

[0025] Ni: As an austenite stabilizing element, nickel can lower the phase transformation temperature and promote the formation of finer microstructures, thereby significantly improving the low-temperature impact toughness of steel. For thick-walled steel plates, nickel can effectively reduce the performance differences from the surface to the core, ensuring the uniformity and toughness of the microstructure throughout the cross-section. In this invention, the Ni content is controlled at 0.10%~0.20%.

[0026] Als: In pipeline steel smelting, aluminum is mainly used as a strong deoxidizer to remove dissolved oxygen from the molten steel, forming Al2O3 inclusions that float to the slag, thereby purifying the molten steel. However, excessive acid-dissolved aluminum can form large Al2O3 clusters, becoming crack initiation points or impairing toughness. Therefore, this invention controls the Al content to 0.010%~0.020%.

[0027] Ca: By feeding calcium wire into molten steel, high-melting-point, angular Al₂O₃ inclusions and easily deformable, elongated MnS inclusions can be transformed into low-melting-point, spherical calcium aluminate composite inclusions, thus refining the inclusion size. Furthermore, the spherical inclusions have minimal impact on anisotropy, improving properties in both the transverse and thickness directions. Therefore, this invention controls the Ca content to be between 0.002% and 0.003%.

[0028] Mg: Magnesium has a strong affinity for oxygen and sulfur in molten steel, effectively reducing their content. It also significantly modifies inclusions such as Al₂O₃ and MnS. The attraction between MgO particles is weaker than that between Al₂O₃ and Ti₂O₃ particles. Therefore, compared to Al₂O₃ and Ti₂O₃, MgO is less prone to agglomeration and growth, tending instead to be dispersed throughout the steel. It has a strong pinning effect on austenite grain boundaries and can also promote the formation of acicular ferrite. Therefore, this invention controls the Mg content to 0.001%~0.002%.

[0029] Ce: After the addition of magnesium and calcium, cerium can further modify inclusions in steel, forming small, dispersed spherical CeAlO3 and Ce2O2S. These oxysulfides have a low lattice mismatch with acicular ferrite, enhancing the ability of oxide particles to promote the nucleation of acicular ferrite. Therefore, the Ce content in this invention is controlled at 0.002%~0.003%.

[0030] A method for manufacturing thick-gauge L555M pipeline steel hot-rolled coils with low yield strength ratio and excellent CTOD performance includes smelting and continuous casting (hot metal pretreatment, converter smelting, ladle refining, LF furnace light desulfurization treatment, Mg-Ca-Ce-Ti composite treatment to control oxide morphology, RH furnace to control hydrogen and oxygen content, and slab continuous casting using electromagnetic stirring or dynamic light reduction), roughing, finishing, cooling, and coiling; specifically including: 1) Smelting and Continuous Casting: After hot metal pretreatment, a top-and-bottom blowing converter is used. Rapid decarburization and dephosphorization are achieved through optimized oxygen supply and bottom-blown argon, with preliminary alloying by adding Mn, Nb, and Ni alloys. Ladle refining employs a light desulfurization process in an LF furnace. In the later stages of refining, Mg, Ca, Ce, and Ti alloy wires are added sequentially to control the quantity and morphology of inclusions, thereby improving plasticity and toughness. After composite treatment, bottom-blown argon is maintained in the ladle for soft stirring, promoting the full flotation of inclusions. The ladle is transferred to an RH station for vacuum circulation degassing of the molten steel, further improving its purity. During continuous casting, electromagnetic stirring is added to disrupt the dendrites in the primary solidified shell, improving surface and subsurface quality. Dynamic light pressure is applied to the solidifying billet in the fan-shaped section to reduce central porosity and improve the quality of the continuously cast billet.

[0031] 2) Rough Rolling: A 200mm thick continuously cast billet is heated to 1170~1200℃ in a walking beam furnace and held for 160~300min, followed by five passes of rough rolling. To achieve a high reduction ratio in the second to fourth passes, the reduction rate in the first pass is controlled below 9%, and the reduction rates in the second to fourth passes are all greater than 27%, with a total reduction rate of 71%~72%. The intermediate billet thickness is 56~58mm. Furthermore, the rough rolling speed in the first pass is controlled below 1.7m / s, and the speed in the second to fifth passes is controlled below 2.6m / s. The final rolling temperature is controlled at 970~1000℃ to ensure it is within the austenite recrystallization zone and to prevent mixed grain formation. The high reduction ratio and low rolling speed in the rough rolling stage allow for sufficient dynamic recrystallization of austenite grains from the surface to the core, achieving the goal of refining the original austenite grains and improving the uniformity of the microstructure. The austenite with an average grain size of 11~18μm obtained by this rough rolling process achieves ultrafine recrystallized austenite and reduces the dependence on the addition of Mo and Cr alloying elements.

[0032] 3) Finishing Rolling: The entry temperature of the finishing mill is controlled at 910~970℃; the finishing mill adopts a seven-pass design, with the reduction rate of each pass being greater than 7%, and the total reduction rate being 61%~62%; during the finishing milling process, the deformation resistance is increased step by step by controlling the reduction rate, ensuring sufficient flattening of austenite grains and dislocation accumulation within the grains to improve strength. The final rolling temperature of the finishing mill is controlled at 735~790℃; 4) Cooling and Coiling: After rolling, a short relaxation period of 10-25 seconds is performed. During relaxation, the dislocations stored within the austenite recover and form more regular and stable subgrain boundaries, providing more nucleation sites for the subsequent acicular ferrite phase transformation and promoting the formation of ultrafine grains. Furthermore, a small amount of polygonal ferrite soft phase is formed during relaxation. The coordinated deformation of the soft and hard phases significantly reduces the yield strength ratio and improves uniform deformation capability. After relaxation, ultra-fast cooling combined with laminar flow cooling is used. The initial cooling temperature is controlled at 730-750℃, the ultra-fast cooling rate is 50-70℃ / s, and the laminar flow cooling rate is 10-20℃ / s. After cooling, a high-strength coiler is used for coiling, with the coiling temperature controlled at 270-400℃.

[0033] This invention employs a Mg-Ca-Ce-Ti composite treatment method during the smelting stage to introduce a large number of nano-sized oxide particles, which pin austenite grain boundaries during heating and holding to prevent grain growth. During the rough rolling stage, increasing the compression ratio and reducing the speed promotes sufficient recrystallization of austenite grains from the surface to the core, providing a fine original structure for subsequent phase transformation. After rolling, a short relaxation time is performed, which introduces a small amount of polygonal ferrite to reduce the plate yield strength ratio and promotes the formation of subgrain boundaries, which, together with the oxide particles inside the austenite grains, provide a large number of sites for the nucleation of acicular ferrite. Ultimately, a product with high strength, low yield strength ratio, and excellent low-temperature CTOD performance is obtained, making it safer during service in low-temperature environments.

[0034] Compared with the prior art, the beneficial effects of the present invention are: 1) The Mg-Ca-Ce-Ti composite treatment method introduces a large number of nano-sized oxide particles into the steel, which hinders the growth of austenite grains during the heating and holding process of the billet. Therefore, even at higher heating temperatures, fine austenite grains can be obtained, reducing the load on the rolling mill and facilitating the implementation of roughing rolling with a large compression ratio.

[0035] 2) By increasing the compression ratio per pass in the roughing stage and reducing the rolling speed, sufficient dynamic recrystallization of austenite grains from the surface to the core is achieved, resulting in an average austenite grain size of 11~18μm. Grain refinement is achieved without adding Mo and Cr elements, giving the product a certain economic advantage.

[0036] 3) After rolling, a short relaxation time is used to promote the formation of a small amount of polygonal ferrite. Through the coordinated deformation of soft and hard phases, the yield strength ratio of the plate and coil is significantly reduced, so that the product has better resistance to large plastic deformation.

[0037] 4) The oxide particles formed during the smelting process and the subgrain boundaries formed during the relaxation process together provide a large number of nucleation sites for the acicular ferrite phase transformation during the cooling stage, promote the formation of ultrafine acicular ferrite structure, and give the product excellent low-temperature CTOD performance. Attached Figure Description

[0038] Figure 1 The image shows the morphology of the rough-rolled austenite grains in Example 1.

[0039] Figure 2 The microstructure of Example 1 consists of polygonal ferrite (PF) + acicular ferrite (AF) + Mao islands (M / A). Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the specific implementation methods of this invention will be further described below in conjunction with the embodiments. The following embodiments are used to specifically illustrate the content of this invention. These embodiments are only general descriptions of the content of this invention and do not limit the content of this invention.

[0041] The chemical composition of Examples 1-10 is shown in Table 1, the heating, rolling and cooling process parameters are shown in Tables 2 and 3, and the mechanical property test results are shown in Table 4.

[0042] Table 1 Chemical composition of steel in the examples (wt%):

[0043] Table 2. Heating and rough rolling process parameters for each embodiment:

[0044] Table 3. Finishing rolling and cooling process parameters for each embodiment:

[0045] Table 4. Main mechanical properties of each embodiment:

[0046] As can be seen from Tables 1-4, by adopting the composition design, rolling and cooling process of the present invention, hot-rolled pipeline steel coils with low yield strength ratio and high CTOD performance at the 555MPa level can be produced.

[0047] This invention employs a C-Mn-Nb-Ni design. Without adding Mo and Cr, a Mg-Ca-Ce-Ti composite treatment method is used during smelting to introduce nanoscale oxide particles that pin austenite grain boundaries during the heating and holding stages of the cast billet, providing a uniform and fine initial microstructure for rolling. In the rough rolling stage, the single-pass compression ratio is increased, and the rolling speed is reduced, allowing for sufficient recrystallization of austenite from the surface to the core. This refinement of austenite grains improves the overall mechanical properties. A short relaxation time is used after rolling to obtain an ultrafine-grained acicular ferrite microstructure, significantly reducing the yield strength ratio while greatly improving low-temperature toughness. Ultimately, this results in thick-gauge L555M pipeline steel hot-rolled coils with a low yield strength ratio and excellent CTOD performance.

Claims

1. A thick-gauge L555M pipeline steel hot-rolled coil with low yield strength ratio and excellent CTOD performance, characterized in that, The chemical composition of the steel, by weight percentage, is as follows: C: 0.040%~0.060%, Si: 0.08%~0.25%, Mn: 1.65%~1.85%, P≤0.019%, S≤0.005%, Nb: 0.065%~0.080%, V: 0.015%~0.035%, Ti: 0.012%~0.022%, Ni: 0.10%~0.20%, Als: 0.010%~0.020%, Ca: 0.002%~0.003%, Mg: 0.001%~0.002%, Ce: 0.002%~0.003%, N≤0.007%, with the balance being Fe and unavoidable impurities.

2. The thick-gauge L555M pipeline steel hot-rolled coil with low yield strength ratio and excellent CTOD performance according to claim 1, characterized in that, The hot-rolled coil has a yield strength of 560~600MPa, a tensile strength of 700~750MPa, a yield strength ratio of ≤0.80, an elongation of ≥30%, an average impact energy of ≥300J at -60℃, an average drop shear area of ​​≥85% at -25℃, and a CTOD value of ≥1.40mm at -25℃.

3. The thick-gauge L555M pipeline steel hot-rolled coil with low yield strength ratio and excellent CTOD performance according to claim 1, characterized in that, The thickness of the hot-rolled coil is 21.4~22mm, and the microstructure consists of polygonal ferrite + acicular ferrite + Mao islands.

4. A method for manufacturing a thick-gauge L555M pipeline steel hot-rolled coil with excellent CTOD performance and low yield strength ratio as described in any one of claims 1-3, comprising smelting and continuous casting, roughing, finishing, cooling and coiling; characterized in that, Specifically, it includes: 1) Metallurgical continuous casting: Mg, Ca, Ce, and Ti alloy wires are added sequentially in the later stage of refining; 2) Rough rolling: The continuously cast billet is heated to 1170~1200℃ and held for 160~300min, followed by five passes of rough rolling; the reduction rate of the first pass is controlled below 9%, the reduction rate of the second to fourth passes is greater than 27%, and the total reduction rate is 71%~72%. The rough rolling speed of the first pass is controlled below 1.7m / s, and the rough rolling speed of the second to fifth passes is controlled below 2.6m / s; the final rolling temperature of the rough rolling is controlled at 970~1000℃. 3) Finishing rolling: The entry temperature of the finishing rolling mill is controlled at 910~970℃; the total reduction rate of the finishing rolling mill is 61%~62%; the final rolling temperature of the finishing rolling mill is controlled at 735~790℃; 4) Cooling and coiling: After rolling, relax for 10~25s. After relaxation, use ultra-fast cooling + laminar flow cooling. The starting cooling temperature is controlled at 730~750℃, the ultra-fast cooling rate is 50~70℃ / s, and the laminar flow cooling rate is 10~20℃ / s. The coiling temperature is controlled at 270~400℃.

5. The method for manufacturing thick-gauge L555M pipeline steel hot-rolled coil with low yield strength ratio and excellent CTOD performance according to claim 4, characterized in that, The smelting and continuous casting process also includes: after pretreatment of molten iron, a top and bottom blowing converter is used, and the ladle is refined using LF furnace light desulfurization treatment; the ladle is transferred to the RH station for vacuum circulation degassing treatment of molten steel; and electromagnetic stirring is added during the continuous casting process.

6. The method for manufacturing thick-gauge L555M pipeline steel hot-rolled coil with low yield strength ratio and excellent CTOD performance according to claim 4, characterized in that, The average austenite grain size in the steel after rough rolling is 11~18μm.

7. The method for manufacturing thick-gauge L555M pipeline steel hot-rolled coil with low yield strength ratio and excellent CTOD performance according to claim 4, characterized in that, The thickness of the intermediate slab between finishing and roughing rolling is 56~58mm.

Citation Information

Patent Citations

  • X80 pipeline steel hot-rolled coil with low yield ratio and manufacture method thereof

    CN102851614A

  • X80 pipeline steel plate with low yield ratio and high toughness and manufacturing method thereof

    CN103276314A

  • High-toughness X80 pipeline steel plate coil with thickness greater than or equal to 18.5mm and production method

    CN104073744A

  • L555M pipeline steel with excellent low-temperature toughness and manufacturing method thereof

    CN108546885A

  • Process method for producing limit specification X80 pipeline steel in high water temperature season

    CN117230287A